High efficiency titanium nitride bowtie nanoparticle and upconverter layer incorporated kesterite tandem solar cell - Nowshin Akhtary; Ahmed Zubair (Results in Physics, 2023)
Thin-film photovoltaic (PV) technology offers an economically viable and flexible way to harness solar energy. Using a material that absorbs more solar light than silicon significantly reduces material consumption and costs. Solar cells based on the kesterite mineral structure and its alloys stand out from other thin-film solar cells due to their earth-abundance and non-toxicity. Incorporating plasmonic nanoparticles in the kesterite absorber layer opens a promising path of enhancing light trapping efficiency. Again, the main losses in solar cells result from the incomplete utilization of the solar spectrum. The otherwise unused sub-bandgap photons can be utilized by adding an upconverting layer on a solar cell. This paper demonstrates a theoretical design and performance analysis of a high-efficiency kesterite solar cell by incorporating titanium nitride (TiN) plasmonic bowtie nanoparticles (NPs) and an upconverter layer. We compared the optical characteristics of various shapes and sizes of nanoparticles to find the optimum solar cell efficiency. The 100 nm thick bowtie-shaped NP had the highest power conversion efficiency, η of 24.80% and had the open circuit voltage Voc=0.59V, and short circuit current density, Jsc = 45.43 mA/cm2. The absorbed power for bowtie-shaped TiN NP incorporation enhanced the average absorption from ∼61% to ∼88% for the kesterite layer. For 100 nm thickness, the absorption enhancement, g, was greater than 1 for the whole spectral range, and the maximum value was ∼1.2. Incorporating a yttrium aluminum garnet upconverter layer increased the solar cell efficiency to ∼27.44.%.